Family Ownership as a Moderator Variable on Board, Leverage, and Environmental Performance - Haninun, Haninun; Damayanti, Tri; Rahayu, Ni Putu Widhia; Aminah, Aminah; Graisman.P, Naufal (Universitas Muhammadiyah Yogyakarta, 2024)
Research Aims: This study aims to examine family-listed companies by determining the effects of leverage, board, and ownership on environmental performance in Indonesia.Design/Methodology/Approach: A total of 130 family-listed companies were examined using the unbalanced panel method. Board resources diversity also stimulated increased strategic opportunities in deciding the companies plans, regarding the conceptual framework prioritizing dependence theory.Research Results: The results showed that leverage and board significantly-negatively and significantly-positively impacted environmental performance, respectively. Family ownership also strengthened both impacts and transformed a negative direction into a positive effect. This strengthening was due to the important role of ownership in decision-making processes, such as the impact on external stockholders and costs related to environmental performance considered a non-financial strategic issue.Theoretical Contribution/Originality: The results obtained contribute to developing the relationship between family ownership, ecological education, expert management board, leverage, and environmental performance in Indonesian family-listed companies, specifically in uncertainty economics. Therefore, future studies should be conducted on family companies in the country, implementing the present experimental outcomes as references.Practitioners/Policy Implications: This study leads us to the belief in agency theory, where the control of shareholders largely influences management decisions and includes environmental issues. According to family business stakeholder method, the participants are the most influential actors majorly affecting decision-making, including decisions to overcome environmental problems. The large leverage observed also proves that management commonly adopts risk-averse behaviour, showing the ability to generate efficient costs and comply with the shareholder control direction.Limitations/Implications: The experimental scope was considered limited, as a detailed case account was not provided due to the inability to track environmental performance levels. Since multiple experimental aspects required subsequent evaluation, the knowledge prioritizing the thinking patterns of management and controlling shareholders about environmental issues was highly recommended.